Menalar Asumsi Takfirisme - Ahmad Muhdhor (Jurnal ICMES, 2017)
This article discusses the paradigm that has been used by terror groups in the name of Islam, that is takfirism, which sees that killing the other party considered as kafir is a religious duty. This article reviews descriptively Ḥātim al-'Awnī's criticism of various assumptions of takfirism. In his explanation, al-'Awnī criticized the textual approach on the reading of the text of revelation because he thinks that textualism that leads them to the classical Khawarij's thought of takfir. The other side that is criticized from the assumption of takfirism is over generalization in interpreting the action of someone that indicates disbelief (kufr) in their oppinion. According to al-'Awnī, there are at least two variables that make the kafir stigma to be invalid. Two things are ignorance and takwil or a different exegesis toward the text. The doer of an action indicating kufr is not proper to be verdicted as kafir if he does it unsubconciously based on his ignorance. Similarly, if he does it based on a different exegesis of the text of revelation so the kafir stigma that againsts him becomes invalid. The other side revealed by al-'Awnī's exposure is that takfirism's thought does exist in the thought construct of Wahabism figures in Saudi Arabia since the era of Muḥammad bin Abdul Wahhāb.